Cyto-morphological investigation of cellular content of peripancreatic liquid accumulations in estimation of the clinical course severity in an acute complicated pancreatitis - V. P. Andriushchenko; D. V. Andriushchenko; O. Yu. Andrushevska; L. M. Kohut (Клінічна хірургія)
Objective. To study up a character and peculiarities of cyto-morphological changes in cellular material of the peripancreatic liquid accumulations (LA) as a criterion of objective estimation of the clinical course severity in an acute complicated pancreatitis (ACP).